2019
DOI: 10.1021/acs.jpcc.9b05953
|View full text |Cite
|
Sign up to set email alerts
|

Computational Evaluation of the Diffusion Mechanisms for C8 Aromatics in Porous Organic Cages

Abstract: The development of adsorption and membrane-based separation technologies toward more energy and cost efficient processes is a significant engineering problem facing the world today. An example of a process in need of improvement is the separation of C8 aromatics to recover para-xylene, which is the precursor to the widely used monomer terephthalic acid. Molecular simulations were used to investigate whether the separation of C8 aromatics can be carried out by the porous organic cages CC3 and CC13, both of whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…The kinetic diameter of the PX molecule is 5.8 Å. 43 If h is chosen to be 5.48 Å, the HS-entering probability will be zero. Considering the planarity of the benzene ring, the molecular structure is extremely anisotropic, and the average pore diameter underestimates the HS-entering probability of the PX molecule.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic diameter of the PX molecule is 5.8 Å. 43 If h is chosen to be 5.48 Å, the HS-entering probability will be zero. Considering the planarity of the benzene ring, the molecular structure is extremely anisotropic, and the average pore diameter underestimates the HS-entering probability of the PX molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic diameter of the PX molecule is 5.8 Å . If h is chosen to be 5.48 Å, the HS-entering probability will be zero.…”
Section: Resultsmentioning
confidence: 99%
“…(e) How about the position of the disordered solvent molecules located within the prefabricated pores? In response to these questions, computational methods have been extended to the field of POCs with a few recent examples that have been successful.…”
Section: Strategic Design Of Porous Organic Cagesmentioning
confidence: 99%
“…In a recent study, molecular dynamics simulations indicated that the imine cage 12 undergoes a structural collapse to a nonporous form, a result which matches (Figure d) well with experimental observations. In addition, by calculating the host–guest interaction energies, molecular dynamics simulations also predict the diffusion mechanisms and selectivity for C8 aromatics in POCs.…”
Section: Strategic Design Of Porous Organic Cagesmentioning
confidence: 99%
“…[47] With a computational model of the molecular or solid-state structure, it is then possible to perform a variety of calculations to determine the properties of the material, such as poretopology, surface area, guest uptake and selectivity. [48] In the solid-state, these are standard simulations that have been widely applied in the field of porous framework simulations. [49] Given that the prediction of solid-state structure is laborious, it is valuable to be able to estimate some properties of the individual molecule from computationally cheaper molecular simulations.…”
Section: Kim Jelfs Is a Senior Lecturer And Royal Societymentioning
confidence: 99%